2014
DOI: 10.1007/s12529-014-9413-7
|View full text |Cite
|
Sign up to set email alerts
|

The Fear-Avoidance Model of Chronic Pain: Assessing the Role of Neuroticism and Negative Affect in Pain Catastrophizing Using Structural Equation Modeling

Abstract: The results offer preliminary evidence that patients presenting with more neurotic symptom and heightened NA probably elicit more catastrophic thoughts about pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 71 publications
3
39
0
2
Order By: Relevance
“…Separately, our studies indicated interactions between pain‐related cognitions and affect, and pain can generate high levels of pain‐related disability (eg,), while work in the United States by Jim et al described unresolved physical symptomatology cascades that maintain distress.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Separately, our studies indicated interactions between pain‐related cognitions and affect, and pain can generate high levels of pain‐related disability (eg,), while work in the United States by Jim et al described unresolved physical symptomatology cascades that maintain distress.…”
Section: Introductionmentioning
confidence: 69%
“…Fatigue, pain, insomnia, mood disturbance, and neuropathies are commonly reported symptoms that physically limit patients, often for many years after treatment ends. They impair return to normal roles and function, generating secondary frustration manifesting as further distress, possibly via catastrophizing processes as they struggle to achieve “normality.” Second, residual symptoms take on ambiguous semiotic roles regarding recovery from or recurrence of cancer making it harder for patients to encapsulate the cancer episode in their life story. Persisting symptoms function as reminders of cancer, potentially prompting fears of recurrence and prevent “moving on.” This inability to both escape limitations and intrusion of reminders of cancer impairs return to normal life activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our hypothesis that neuroticism would be positively associated with maladaptive coping was partly supported. We found neuroticism to be strongly associated with symptom catastrophizing, which is in accordance with the literature on single FSS (Drossman et al ., ; Martinéz, Sanchéz, Miro, Medina, & Lami, ) and chronic pain (Wong et al ., ). Other maladaptive coping styles such as distancing, ignoring pain, and distraction were not associated with neuroticism.…”
Section: Discussionmentioning
confidence: 97%
“…However, it is also possible that symptoms of depression may stimulate fear-avoidance pathways. For example, recent data indicate that pain and depression may interact to promote a negative bias toward health in formation [53], and that negative affect may enhance catastrophic thinking and fear-avoidance beliefs [24,54]. There is also some evidence that anxiety disorders tend to precede the onset of chronic pain [55], and that persons with remitted anxiety or depression continue to demonstrate greater pain intensity and disability than persons with no history of anxiety or depression [56].…”
Section: Psychosocial Factors Relevant To Pain-related Fear and Disabmentioning
confidence: 99%